Предмет: Алгебра, автор: NastyaLisgrin

Вычислите значение выражения: ​

Приложения:

Ответы

Автор ответа: Miroslava227
1

Ответ:

1.

 -  \sin( \frac{\pi}{2} )  \times (2tg \frac{\pi}{4}  -  \cos( \frac{\pi}{6} ) ) =  \\  =  - 1 \times (2 \times 1 -  \frac{ \sqrt{3} }{2} ) =  - (2 -  \frac{ \sqrt{3} }{2} ) =  \\  =  \frac{ \sqrt{3} }{2}  -2

2.

ctg \frac{\pi}{6}  \times ( \sin( \frac{\pi}{3} )  - 3 \cos( \frac{\pi}{3} ) ) =  \\  =  \sqrt{3}  \times ( \frac{ \sqrt{3} }{2}  - 3 \times  \frac{1}{2} ) =  \\  =  \sqrt{3}  \times  \frac{ \sqrt{3}  - 3}{2}  =  \frac{3 - 3 \sqrt{3} }{2}

3.

 \cos( \frac{\pi}{4} )  \times (2ctg \frac{\pi}{4}  - 3 \sin( \frac{\pi}{6} ) ) =  \\  =  \frac{ \sqrt{2} }{2}  \times (2 \times 1 -  \frac{3}{2} ) =  \\  =  \frac{ \sqrt{2} }{2}  \times  \frac{1}{2}  =  \frac{ \sqrt{2} }{4}

Похожие вопросы